2021
DOI: 10.3390/biom11030417
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Signatures for Colorectal Cancer Diagnosis and Progression Using UPLC-QTOF-ESI+MS

Abstract: Metabolomics coupled with bioinformatics may identify relevant biomolecules such as putative biomarkers of specific metabolic pathways related to colorectal diagnosis, classification and prognosis. This study performed an integrated metabolomic profiling of blood serum from 25 colorectal cancer (CRC) cases previously classified (Stage I to IV) compared with 16 controls (disease-free, non-CRC patients), using high-performance liquid chromatography and mass spectrometry (UPLC-QTOF-ESI+ MS). More than 400 metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…In our review, most studies employed a type of mass spectrometry analysis, with three studies employing 1 H-NMR analysis [29,42,53]. Liquid-Chromatography-Mass Spectrometry (LCMS), including Ultra-High Performance Liquid Chromatography-Mass Spectrometry (UHPLC-MS) and Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS), was the most popular method for analysis, with eighteen identified studies that applied this technique [22][23][24]26,30,31,33,35,36,38,39,41,43,[47][48][49][50]52], followed by Gas Chromatography-Mass Spectrometry, which was conducted in seventeen studies [24,25,27,28,34,38,39,[44][45][46][48][49][50][51]54,56,57] (Figure 2b). These counts include four studies conducting both LCMS and GCMS.…”
Section: Analytical Methods and Their General Performancementioning
confidence: 99%
See 4 more Smart Citations
“…In our review, most studies employed a type of mass spectrometry analysis, with three studies employing 1 H-NMR analysis [29,42,53]. Liquid-Chromatography-Mass Spectrometry (LCMS), including Ultra-High Performance Liquid Chromatography-Mass Spectrometry (UHPLC-MS) and Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS), was the most popular method for analysis, with eighteen identified studies that applied this technique [22][23][24]26,30,31,33,35,36,38,39,41,43,[47][48][49][50]52], followed by Gas Chromatography-Mass Spectrometry, which was conducted in seventeen studies [24,25,27,28,34,38,39,[44][45][46][48][49][50][51]54,56,57] (Figure 2b). These counts include four studies conducting both LCMS and GCMS.…”
Section: Analytical Methods and Their General Performancementioning
confidence: 99%
“…Other methods of analysis included direct infusion mass spectrometry (1 study) [32], Capillary electrophoresis-time of flight mass spectrometry (CE-TOFMS) (3 studies) [37,40,55], and Matrix Assisted Laser Desorption Ionization-Time of Flight mass spectrometry (MALDI-TOF MS) (1 study) [58] (Figure 2b). Thirty studies [23][24][25][27][28][29][30][31][32][34][35][36][37][38][39][40][42][43][44][45][46][48][49][50]53,54,[56][57][58] employed untargeted metabolomic profiling, while 9 studies employed targeted metabolomics, either with a metabolite subset in mind to begin the study or as part of a validation of their untargeted data [22,25,26,28,35,47,51,52,55]. Of studies where the selections of analytical columns could be identified, 16 used a column that could identify polar and nonpolar compounds …”
Section: Analytical Methods and Their General Performancementioning
confidence: 99%
See 3 more Smart Citations